Ankle foot orthoses for young children with cerebral palsy: a scoping review. Issue 5 (27th February 2021) - Firouzeh, Pegah; Sonnenberg, Lyn K.; Morris, Christopher; Pritchard-Wiart, Lesley
Abstract: Aim: To describe research on outcomes associated with early Ankle Foot Orthosis (AFO) use, AFO use patterns, and parent and clinician perspectives on AFO use among young children with cerebral palsy. Method: Arksey and O'Malley's five-stage method was used to conduct a scoping review. MEDLINE (Ovid), PubMed, CINAHL, Cochrane Database of Systematic Reviews, EMBASE, PEDro, Web of Science and Scopus were searched for studies evaluating AFO use with children under the age of six years. Descriptive information was extracted and outcomes categorized according to the International Classification of Functioning, Disability and Health (ICF). Quality assessments were conducted to evaluate methodological rigor. Results: Nineteen articles were included in the review; 14 focused on body functions and structures, seven on activity level outcomes and no studies addressed participation outcomes. Evaluations of the effects of AFOs on gross motor skills other than gait were limited. Overall, the body of evidence is comprised of methodologically weak studies with common threats to validity including inadequate descriptions of study protocols, AFO construction, and comparison interventions. Conclusion: Research evaluating the effects of AFOs on age-appropriate, functional outcomes including transitional movements, floor mobility and participation in early childhood settings is needed to inform practice regarding early orthotic prescription. Implications for rehabilitation: Lack of rigorous evidence about the effects of AFOs in young children limits the ability of research to guide practice in pediatric rehabilitation. More rigorous research that evaluates a broader range of age-appropriate outcomes, including those focused on participation in meaningful activities, could further inform clinical practice. While clinicians often discuss expectations and goals with individual families, qualitative research that provides more insight into the experiences of families could guide AFO prescription and monitoring practices.